2017
DOI: 10.1002/biof.1351
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation modulates apoptotic processes in thyroid follicular cells

Abstract: Selenium (Se) is an essential micronutrient modulating several physiopathological processes in the human body. The aim of the study is to characterize the molecular effects determined by Sesupplementation in thyroid follicular cells, using as model the well-differentiated rat thyroid follicular cell line FRTL5. Experiments have been performed to evaluate the effects of Se on cell growth, mortality and proliferation and on modulation of pro-and antiapoptotic pathways. The results indicate that Sesupplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A possible mechanism for the beneficial effect of Se in HT is associated with the role of selenoenzymes in immunoregulatory processes, involving T cells activity and cytokine production. In line with this explanation, sodium selenite dose‐dependently inhibited HLA‐DR molecule expression of thyrocytes induced by IFN‐γ, and prevented apoptosis of thyroid follicular cells by TNF antagonism 40,41 . In a Polish study, the addition of selenomethionine (SeMet) to levothyroxine treatment inhibited lymphocyte release of IL‐2, IFN‐γ, and TNF, which was accompanied by a reduction of CRP 31 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A possible mechanism for the beneficial effect of Se in HT is associated with the role of selenoenzymes in immunoregulatory processes, involving T cells activity and cytokine production. In line with this explanation, sodium selenite dose‐dependently inhibited HLA‐DR molecule expression of thyrocytes induced by IFN‐γ, and prevented apoptosis of thyroid follicular cells by TNF antagonism 40,41 . In a Polish study, the addition of selenomethionine (SeMet) to levothyroxine treatment inhibited lymphocyte release of IL‐2, IFN‐γ, and TNF, which was accompanied by a reduction of CRP 31 .…”
Section: Discussionmentioning
confidence: 78%
“…In line with this explanation, sodium selenite dose‐dependently inhibited HLA‐DR molecule expression of thyrocytes induced by IFN‐γ, and prevented apoptosis of thyroid follicular cells by TNF antagonism. 40 , 41 In a Polish study, the addition of selenomethionine (SeMet) to levothyroxine treatment inhibited lymphocyte release of IL‐2, IFN‐γ, and TNF, which was accompanied by a reduction of CRP. 31 Another Italian trial showed that supplementation with SeMet downregulated the IFN‐γ‐inducible chemokines (CXCL9 and CXCL10).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of selenoproteins, including GPx1 is known to mitigate inflammation and bolster immunity that involves down-regulation of COX-2 and mPGES-1, while upregulating H-PGDS to effect a process called “eicosanoid class switching mechanism” in Se stimulated RAW264.7 cells (Yui, Imataka, Nakamura, Ohara, & Naito, 2015; Duntas, 2009; Vunta et al, 2007). Higher Se supplementation up to 2 µM in the form of sodium selenite is also reported to inhibit NFκB-dependent transcription (Nettore et al, 2017; Meplan et al, 2016; Youn et al, 2008; Maehira, Mivagi, & Eguchi, 2003). Se deficient conditions, there is increased ROS generation that is closely associated with increased inflammatory genes, which results in augmentation of oxidative stress in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Its anticancer role has been recently demonstrated [60], as well as the ability to act as antiapoptotic factor in thyroid follicular cells [61]. Its natural source is soil, plants, microorganisms, animals, and sea salt, but sulfur emitted by volcanoes competes with selenium compounds for uptake by plants, causing a decrease in available selenium [22].…”
Section: Volcanic Areamentioning
confidence: 99%